Possibilities of care for serodiscordant couples for HIV who got pregnant - Tassiane Ferreira Langendorf; Ivis Emília de Oliveira Souza; Stela Maris de Mello Padoin; Cristiane Cardoso de Paula; Ana Beatriz Azevedo Queiroz; Maria Aparecida Vasconcelos Moura; Maria Carmen Simões Cardoso de Melo; Lúcia de Fatima da Silva
ABSTRACT Objective: Understanding the meaning of pregnancy for heterosexual couples facing serodiscordant situation for HIV, aiming at construction of care possibilities based on subjectivity. Method: Phenomenological research, theoretical-philosophical-methodological framework by Martin Heidegger. Research was conducted in a University Hospital in the countryside of Southern Brazil, from September 2013 to May 2014 through a phenomenological interview, with participation of eleven couples. Results: For the couples, pregnancy is part of life when they wish to have a child, even when one or both of them already have children from previous relationships. In addition, it is part of life when they consider the risks and do not want to have children in such circumstances anymore, but it happened unexpectedly. Conclusion: Understanding reproductive needs and demands of these couples is an aid for qualification and improvement of care as a contribution to nursing care planning towards reproductive health of these couples.